PENGARUH CELEBRITY ENDORSER PADA MEDIA SOSIAL INSTAGRAM TERHADAP MINAT PEMBELIAN PRODUK LAZETA SKIN CARE DI MAKASSAR - Yuswari Nur (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to: (a) to know the influence of truthwothiness on endorser in social media instagram to interest of purchasing product Lazeta skin care (b) to know influence of attractiveness at endorser in social media instagram to interest of purchasing product Lazeta skin care (c) to know the effect of expertise on endorser in social media instagram to interest of purchasing Lazeta skin care produc (d) to determine the simultaneous influence of all variables on interest in purchasing Lazeta skin care products. This research was conducted at Lazeta skin care of Makassar City by using quantitative method and data collection technique through questionnaire with likert scale that has passed the validity and realibility test with the number of samples of 82 respondents. The data were analyzed by multiple linear regression using SPSS 21. The results of this study indicate that (a) Truthwothiness has significant effect on purchasing interest, (b) Attractiveness has significant effect on purchasing interest, (c) Expertise has significant effect on purchasing interest (d) Truthwothiness, Attractiveness and Expertise influence simultaneously or together to interest in purchasing Lazeta skin care product in Makassar.